PIC simulation of a periodically dielectric loaded millimeter wave gyro-twystron amplifier - Yadav S.G.; Singh A.S.; Thottappan M. (My University, 2025)
A periodically dielectric loaded W-band gyro-twystron has been designed and studied for its beam-wave interaction behavior using a commercially available Particle-In-Cell (PIC) code 'CST Particle Studio'. The present gyro-twystron is operated in circular TE01mode and driven by the DC voltage of 57kV and 5A of electron beam current. The dielectric loading in the output section suppresses the spurious backward wave modes, including TE11, TE21, and second harmonic TEo2 modes. The PIC simulation of the present dielectric loaded gyro-twystron produced a peak RF output power of 84 kW at 94 GHz in TE01mode. The power conversion efficiency and the saturated gain are calculated as 29 % and 32 dB, respectively. © 2019 IEEE.